Enhanced Passive Keyless Car Door Locking System Using Fingerprint - A Halim, Muhammad Hazmie; Sy Ki, Sim (Evolution in Electrical and Electronic Engineering, 2023)
The method of using traditional keys these days is still convenient and acceptable as it is used widely worldwide by car users. However, the way of using traditional keys might cause theft as it faces several security issues and difficulties. So, this project will introduce an enhanced passive keyless car door locking system using fingerprints. By doing away with physical keys and implementing biometric authentication, the system seeks to offer increased security and convenience. This project uses Arduino Uno, a fingerprint sensor, a relay and an actuator car lock as the main components. The application of the system uses a fingerprint sensor to embed the car, and only a valid fingerprint has access to lock and unlock the car. The fingerprint is commonly used by enrolling the fingerprint by using a sensor for fingerprint recognition. A security system was also added to this proposed system as the buzzer will turn on when the invalid fingerprint is attached 3 times. These ideas are chosen due to the user-facing problems in unlocking the door as the key is missing or lost. This project will use a battery as the main supply and a car door lock actuator as the output of the project. To validate the outcome of the proposed keyless car door locking system, the actuator will lock and unlock when verifying the valid fingerprint.